Exploring the substitution of cannabis for alcohol and other drugs among a large convenience sample of people who use cannabis - Chris Wilkins; Jose Romeo; Marta Rychert; Thomas Graydon-Guy (BMC, 2024)
Abstract Background The substitution of cannabis for alcohol and other drugs has been conceptualised in a harm reduction framework as where cannabis is used to reduce the negative side-effects, addiction potential, and social stigma of other drugs. There is currently mixed evidence with recent reviews suggesting cannabis co-use patterns may vary by age and ethnicity. Yet few studies have had large enough samples to examine this demographic variation in detail. Aims To explore the co-use of cannabis with alcohol and other drugs within demographic subgroups of a large sample of people who use cannabis. Specifically: (1) whether cannabis is being substituted for other drugs, and (2), whether cannabis use leads to more, less or the same level of other drug use. Method Online convenience survey promoted via Facebook™ completed by 23,500 New Zealand respondents. Those who had used cannabis and any of eight other substances in the same six-month period were asked if their use of cannabis had any impact on their use of each other substance ("a lot more", "little more", "no impact/same", "little less", "a lot less"). Frequency and quantity used of each other drug was compared by co-use group. Generalised logistic regression models were developed to predict co-use categories. Results Significant proportions reported cannabis use led to "less" alcohol (60%), synthetic cannabinoid (60%), morphine (44%) and methamphetamine (40%) use. Those who reported using "less" had lower frequency and amount used of other drugs. Approximately seven-out-ten reported cannabis use had "no impact" on LSD, MDMA, and cocaine use. One-in-five reported using cannabis led to "more" tobacco use. Young adults (21-35-years) were more likely to report cannabis use led to "less" drinking and methamphetamine use. Adolescent co-users (16-20 years) reported mixed impacts. Māori were more likely to report cannabis use resulted in "less" alcohol, tobacco, methamphetamine, and LSD use. Students and those living in cities were less likely to report cannabis use lowering use of other substances. Conclusion Cannabis and other drug co-use patterns are moderated by life stages, lifestyles, cultural perspectives, and urbanicity. Harm reduction initiatives and policy reforms should take account of these moderating factors.